(3GdJNWjW GdEbJUGOj Ydi GdeSJhi GdLeYj (B/s - (3HGhdR, QhLQ Cs; (3c(B.(3hHffR, OjajO s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1994)
(3GdEbJUGO GdLeYj hGdJNWjW,GdMGLI Edi GdJNWjW,ETJbGb GdCgOGa GdJNWjWjI,WHjYI GdEbJUGO,GdMdhd GdeKdi,GdJNWjW GdGbJUGOj aj GdhGbY GdYedj,GdJNWjW GdEbJUGOj hGfLGRGJg aj GdeedcI GdYQHjI GdSYhOjIs
(3cTGa GdeUWdMGJ(B:(3U(B.219-221s
Keywords: (3GdJNWjW GdEbJUGOjs